2017
DOI: 10.5194/gmd-10-2333-2017
|View full text |Cite
|
Sign up to set email alerts
|

Modeling regional air quality and climate: improving organic aerosol and aerosol activation processes in WRF/Chem version 3.7.1

Abstract: Abstract. Air quality and climate influence each other through the uncertain processes of aerosol formation and cloud droplet activation. In this study, both processes are improved in the Weather, Research and Forecasting model with Chemistry (WRF/Chem) version 3.7.1. The existing Volatility Basis Set (VBS) treatments for organic aerosol (OA) formation in WRF/Chem are improved by considering the following: the secondary OA (SOA) formation from semi-volatile primary organic aerosol (POA), a semi-empirical formu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 86 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…The SOA particle volatility in single-precursor systems has been investigated based on the aerosol evaporation after heating (Lopez-Hilfiker et al, 2015;Donahue et al, 2006) by isothermal dilution (Yli-Juuti et al, 2017) or a combination of the two (Louvaris et al, 2017;Cain et al, 2020). Previous works have shown that the oxidation of α-pinene results in low-volatility and semi-volatile components (Zhang et al, 2015), while extremely low-volatility material could be formed from oligomerization reactions (Lopez-Hilfiker et al, 2015).…”
mentioning
confidence: 99%
“…The SOA particle volatility in single-precursor systems has been investigated based on the aerosol evaporation after heating (Lopez-Hilfiker et al, 2015;Donahue et al, 2006) by isothermal dilution (Yli-Juuti et al, 2017) or a combination of the two (Louvaris et al, 2017;Cain et al, 2020). Previous works have shown that the oxidation of α-pinene results in low-volatility and semi-volatile components (Zhang et al, 2015), while extremely low-volatility material could be formed from oligomerization reactions (Lopez-Hilfiker et al, 2015).…”
mentioning
confidence: 99%
“…Journal of Advances in Modeling Earth Systems mentation branching ratio increases in their study. Previous studies using this scheme implemented in the regional Weather Research and Forecasting model with Chemistry (WRF-Chem) suggested that organic aerosol (OA) loadings in the eastern United States and central Mexico could be reduced by a factor of 2 when the fragmentation branching ratio increases 40% (Shrivastava et al, 2013;Yahya et al, 2017).…”
Section: 1029/2020ms002266mentioning
confidence: 99%
“…Previous modeling studies report a large sensitivity of simulated SOA to the branching ratio between functionalization and fragmentation (Glotfelty et al, 2017;Hermansson et al, 2014;Murphy et al, 2012;Shrivastava et al, 2013Shrivastava et al, , 2015Yahya et al, 2017). Using the Community Atmosphere Model Version 5 (CAM5) incorporated within the Community Earth System Model (CESM), Shrivastava et al (2015) estimated that the global SOA production decreases from 502 to 87 Tg/yr when empirical SOA formulations turn gas-phase fragmentation on.…”
Section: Introductionmentioning
confidence: 99%
“…The Weather Research and Forecasting model with Chemistry (WRF/Chem) was originally co-developed by U.S. National Center for Atmospheric Research and National Oceanic and Atmospheric Administration and further developed by scientific communities [32]. WRF/Chem v3.7.1 =by the North Carolina State University (NCSU) (WRF/Chem-NCSU) is based on the NCSU's version of WRF/Chem v3.7.1 [41,42]. WRF/Chem v3.7.1-ROMS is based on the NCSU's version of WRF/Chem v3.7.1 coupled with the Regional Ocean Modeling System (ROMS) (WRF/Chem-ROMS) [40].…”
Section: Model Descriptionmentioning
confidence: 99%